The role of exerkines on brain mitochondria: a mini-review - Heo, Junwon; Noble, Emily E.; Call, Jarrod A. (Journal of applied physiology (1985), 2023)
Exercise benefits many organ systems, including having a panacea-like effect on the brain. For example, aerobic exercise improves cognition and attention and reduces the risk of brain-related diseases, such as dementia, stress, and depression. Recent advances suggest that endocrine signaling from peripheral systems, such as skeletal muscle, mediates the effects of exercise on the brain. Consequently, it has been proposed that factors secreted by all organs in response to physical exercise should be more broadly termed the “exerkines.” Accumulating findings suggest that exerkines derived from skeletal muscle, liver, and adipose tissues directly impact brain mitochondrial function. Mitochondria play a pivotal role in regulating neuronal energy metabolism, neurotransmission, cell repair, and maintenance in the brain, and therefore exerkines may act via impacting brain mitochondria to improve brain function and disease resistance. Therefore, herein we review studies investigating the impact of muscle-, liver-, and adipose tissue-derived exerkines on brain cognitive and metabolic function via modulating mitochondrial bioenergetics, content, and dynamics under healthy and/or disease conditions.